(untitled) (Eurasian Research Bulletin, 2022)
This article discusses the improvement of designs and technologies in order to create more reliable, economical machines. Gears are included in the design of almost all types of modern machines. High-quality manufacturing of gears affects the level of the state of technology in all branches of engineering. The main difficulties in the practical use of gears in mechanical engineering is the complication and increase in the cost of the technological process of their manufacture and assembly. Currently, much attention is paid to the improvement of the geometric shapes of the gear teeth. In mechanical engineering, involute gears are widely used, they have an increase in their load capacity and improve dynamic characteristics by optimizing geometric parameters